Analisis Ilmu Balaghah Terhadap Gaya Bahasa Perumpamaan Dalam Al-Qur’an - Idris Siregar; Nada Muhsinati; Rais Nashrul Khair; Ananda Firmansyah (Journal of Innovative and Creativity, 2026)
The purpose of this research is to examine the Qur'anic text's figurative language (parables) through the lens of Balaghah, the Arabic science of rhetoric, in order to decipher its profound significance. The study utilizes a descriptive qualitative approach, systematically analyzing Qur'anic texts according to Balaghah principles, including isyarah (figurative expression), tasybih (simile), and isti’arah (metaphor). The findings show that the Qur'anic use of parables serves multiple purposes: it explains abstract ideas, makes people feel something, and reinforces Islamic teachings. This study highlights the importance of comprehending Balaghah for scholars and readers of the Qur'an in order to understand its rhetorical beauty and implied meanings, which in turn enhances the depth and breadth of Qur'anic study and interpretation.